Induksi Kalus dari Eksplan Daun In Vitro Keladi Tikus (Typhonium sp.) dengan Perlakuan 2,4-D dan Kinetin - Marlina Agustina Sitinjak; Mayta Novaliza Isda; Siti Fatonah (Al-Kauniyah: Jurnal Biologi, 2015)
Rodent tuber (Typhonium sp.) belongs to Araceae that has a potential as medicinal plant. This procedure takes a long periode to produce a large quantity of plant. Therefore, an in vitro propagation using callus culture is necessary to solve this problem.  This research aimed to determine the best concentration of 2,4-D and kinetin to induce callus of in vitro leaf rodent tuber explants. This research used in vitro leaft explants of rodent tuber with MS medium.  The design used is Randomize Group Design with 10 treatment. The results showed that explants could not produce callus, the explants response just a swelling leaf explants. The treatment that could give up to 100% swelling response was 2.4-D 0.5 mg / L dan 1 mg / L and the combination treatment 0.5 mg / L 2.4-D + 0.3 mg /L kinetin, 0.5 mg / L 2.4-D + 0.5 mg / L kinetin and 1.5 mg / L 2.4-D + 0.5 mg / L kinetin.   The treatments that could maintain 66.67% explants growth was the combination 0.5 mg / L 2.4-D + 0.5 mg / L kinetin and 1 mg /L 2.4-D + 0.5 mg / L kinetin.